(untitled) (The Review of Diabetic Studies, 2023)
Obesity is associated with an increased risk of type 2 diabetes (T2D). Pancreatic beta-cell failure is an early event in the development of glucose dysregulation and diabetes. Interventions to halt beta-cell failure in T2D include diet modification, exercise, and use of pharmacologic agents. There is evidence that abdominal obesity may contribute to diabetes through insulin resistance and beta-cell impairment. Pivotal long-term studies into the prevention of T2D have shown the importance of weight loss beside diet, lifestyle, and medication. The Finnish Diabetes Prevention Program (DPP) showed that weight loss gradually reduces the risk of diabetes, and that even modest weight loss can significantly reduce the incidence of T2D. Similarly, in the US DPP, weight loss as part of intensive lifestyle modification was the major factor in reducing the incidence of T2D in high-risk subjects, being more effective than drug intervention. While understanding the relationship between obesity and diabetes is complex, we know that weight loss has positive effects on adipose tissue. It causes an increase in the beneficial fat cell hormone adiponectin, and a decrease in adipose tissue inflammation. Also, it is associated with reduced insulin resistance and a consequential reduction in glucolipotoxicity, which can improve beta-cell function. In summary, weight loss improves glycemic control and thereby mitigates diabetes symptoms and complications, possibly through the preservation of beta-cell function. Therefore, efforts to prevent diabetes and preserve beta-cell function in patients with T2D should more consequently emphasize and target weight loss.